HUBUNGAN MOTIVASI KERJA TERHADAP KINERJA GURU SDN 056426 SIDODADI GERGAS - Suleiman (Journal of Community Devation, 2025)
This research aims to find out: 1) Is there a positive and significant relationship with the effectiveness of Madrasah head leadership on teacher performance, 2) Is there a positive and significant relationship with work motivation on teacher performance, 3) Is there a positive and significant relationship with the effectiveness of madrasah head leadership and work motivation together on teacher performance. This type of research is quantitative research with the research location at SDN 056426 Sidodadi Gergas. The research sample calculation was carried out based on the Kriechie Morgan table, namely 153 people. The research results show that: 1) There is a positive and significant contribution between the leadership effectiveness variable (X1) on teacher performance (Y). With a score obtained from the trend test results of 76.4% in the moderately high category, the results of a simple correlation calculation were obtained at 0.485>0.158 at a moderate level of relationship between the leadership effectiveness variable (X1) and teacher performance (Y). 2) There is a positive and significant contribution between the teacher work motivation variable (X2) on teacher performance (Y). With a score obtained from the trend test results of 82.4% in the moderately high category, the results of a simple correlation calculation were 0.790>0.158 at a high level of relationship between the teacher work motivation variable (X2) and teacher performance (Y). 3) There is a positive and significant contribution between the variables of leadership effectiveness (X1) and teacher work motivation (X2) together. To teacher performance (Y), the R Square value (coefficient of determination) is obtained at 0.716 = 71.6%. The results of the multiple regression equation test also obtained the value of each variable, the magnitude of the irregression coefficient (β) leadership effectiveness (X1) = 0.304, teacher work motivation (X2) = 0.280, so that the hypothesis obtained is that there is a positive and significant contribution between the variables leadership effectiveness (X1) and teacher work motivation (X2) on teacher performance (Y). So it can be interpreted that the better the leadership exemplified by the madrasa head and the motivation given to the teachers at SDN 056426 Sidodadi Gergas, the better the teacher performance (Y).